(untitled) (Research, Society and Development, 2021)
The cashew tree is a tree native to the Northeastern coast in Brazil, of great economic, nutritional and cultural representation in the region. The article aims to promote information about cashews as a source of relevant nutrients for maintaining health in periods of prolonged drought and the economic obstacles faced by cashew cultivation, through a bibliographic review of scientific literature on the subject. Cashew is made up of pseudofruit, a fleshy and juicy part, rich in vitamin C and fiber, and its true fruit, the chestnut, an important source of energy and nutrients in the diet. The cashew nut has a prominent place as an export product in Brazil, however in recent years due to phytopathologies, pests, long droughts and problems in its processing have led to the decline of its economic position, causing the fall of Brazil’s competitiveness as an exporting country of this product. Governmental measures that value the consumption of national fruits, focusing on their nutritional and cultural value can help the economic recovery of this cultivate.